UJI PRAKTIKALITAS PENGGUNAAN ANDROID MOBILE LEARNING DALAM PEMBELAJARAN FISIKA KELAS XI PADA MATERI SUHU DAN KALOR - Rahmad, M; Syafi’i, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to examine the practicality of android mobile learning as a medium for high school physics learning. The research method used was research and development (R & D). In this study android mobile learning was tested for the practicality by 20 students and 2 physics teachers of SMAN 5 Pekanbaru. Based on data analysis, Android Mobile Learning can be used to help improve the learning process obtained by practical values with very high categories for teachers. The results of practical tests according to students, android mobile learning make it easy to study temperature and heat with practicality scores in the high category. Based on the data obtained, android mobile learning is very practical for students and teachers to be used in the learning process.Key Words: Android Mobile learning, practicality, Temperature and Calor.